HUBUNGAN PENGETAHUAN DAN SIKAP REMAJA PUTRI DALAM KESIAPAN MENGHADAPI MENARCHE DI SDN 111 PEKANBARU - Zalni, Rummy Islami; Aldinda, Tharra Widadari; Anita, Wan; Pesa, Yadriati Maya; Ayuni, Marina Sri (Ensiklopedia of Journal, 2024)
The beginning of menstruation is a traumatic event for some young women who do not prepare early. Young women need information about the menstrual cycle and menstrual health. The purpose of this study was to determine the relationship between knowledge and attitudes of young women in readiness for menstruation at SDN 111 Pekanbaru. This research was conducted on July 28 –  07 August 2023, this type of research is analytic in nature with a Cross-Sectional survey design, a sample size of 63 respondents. The results of the analysis used the Chi-square test with α 0.05 and p value 0.004 (p <0.05) meaning that there is a significant knowledge relationship between attitudes and readiness to face menarche. The researcher's suggestions are expected for students who will experience menarche to prepare themselves to face this phase, so that students are better prepared to face the menstrual period, and for School Teachers at SDN 111 Pekanbaru especially for Counseling Guidance (BK) teachers as an Additive to Improve Extension Programs to female students in introducing events about menarche.Keywords: Menarche, Knowledge, Attitude